Dampak kualitas layanan, kepercayaan, dan perceived switching cost terhadap loyalitas pelanggan Provider Smartfren di Kota Semarang - Syaifuddin, Mukhammad; Putra, Febrianur Ibnu Fitroh Sukono; Aqmala, Diana; Ulfa, Adiila Kustya (Journal of Management and Digital Business, 2025)
Technological advancements are primarily driven by globalization, which continues to evolve. This development influences people’s patterns of thinking and behavior, particularly in communication, making it easier for individuals to carry out work-related and personal activities. According to a study by We Are Social, 185 million Indonesians were internet users as of January 2024. This study examines the influence of service quality, trust, and perceived switching costs on customer loyalty. The research focuses on residents of Semarang City who have used Smartfren services, with a total sample of 112 respondents collected via Google Forms shared through WhatsApp. The study employs primary data using a non-probability sampling method. The data analysis technique uses multiple linear regression. The results of the analysis indicate that service quality and trust both have a positive and significant influence on customer loyalty. At the same time, perceived switching costs also show a favorable and substantial impact on customer loyalty.